Mosaic variant in ATP2C1 presenting as relapsing linear acantholytic dermatosis. (1st July 2020) - Katzman, J.A.; Chavan, R.; Holliday, A.C.; Coman, G.; Grider, D.; Kolodney, M.S.
Summary: Relapsing linear acantholytic dermatosis (RLAD) is a rare disease that manifests as recurring episodes of crusted and vesicular lesions distributed in a Blaschkoid pattern with histology resembling Hailey–Hailey disease. RLAD, in the presence of generalized disease, has been shown to be a type 2 mosaic form of Hailey‐Hailey disease. RLAD, without systemic disease, has been hypothesized to be type 1 mosaic Hailey‐Hailey disease, but this assertion has lacked genetic conformation. To determine the genetic abnormalities causing RLAD, we performed exome sequencing of affected tissue and blood in one patient. Exome sequencing of a punch biopsy revealed a c.238A>T, p.(Lys80*) variant in ATP2C1 found in 26% of the reads from lesional skin but absent in germline DNA. This somatic variant causes a truncated protein that would likely result in loss of function. Our findings indicate that, in this patient, RLAD is a clinical presentation of type 1 segmental Hailey–Hailey disease. What's already known about this topic? Relapsing linear acantholytic dermatosis (RLAD) is postulated to be a mosaic form of Hailey–Hailey disease. This hypothesis has remained unproven for type 1 disease and the putative gene and driving genetic variants have remained unknown. What does this study add? Exome sequencing, performed on lesional skin and matched blood, found RLAD lesions to be mosaic for variants causing a premature stop codon in ATP2C1 . Our findings support the hypothesis that RLAD is a type 1 segmental form of Hailey–Hailey disease caused by postzygotic variants in ATP2C1 . Linked Comment: Darling. Br J Dermatol 2020; 183 :14–15 .